Comment on "Seaweed ecosystems may not mitigate CO2 emissions" by Gallagher et al. (2022). (19th May 2022) - Stafford, R
Abstract: The role of animal (and plant) respiration in assessing the true carbon sequestration potential of a system is vital to acknowledge, and addressed in Gallagher et al . (2022). However, within this article, there is confusion around the respiration of kelp once exported to open waters from kelp ecosystems but respired before sequestration. From their consideration of a closed kelp ecosystem (but with import of phytoplankton and export of kelp), respiration of phytoplankton transported into the system is correctly considered in their net respiration figures (but not the fixation of carbon dioxide by the phytoplankton outside the system, again correct for a closed system). However, the respiration of kelp exported from the closed system is also considered as part of the kelp community respiration. A closed system must remove this respiration of exported kelp from calculations. Alternatively, an open system must consider also the carbon fixation by phytoplankton. The outcome of redefining open and closed systems is that the systems examined in Gallagher et al . (2022) will be net sinks of carbon, although, as yet, the magnitude of this sink is poorly quantified.